2015
DOI: 10.4049/jimmunol.1401661
|View full text |Cite
|
Sign up to set email alerts
|

Early Development in the Peritoneal Cavity of CD49dhigh Th1 Memory Phenotype CD4+ T Cells with Enhanced B Cell Helper Activity

Abstract: The Th cells that regulate peritoneal B-1 cell functions have not yet been well characterized. To address this question, we investigated peritoneal CD4+ T cells, observed a high frequency of the conjugates of B-CD4+ T cells in the peritoneal cavity, and identified a population of CD49dhighCD4+ T cells that constituted about half of all CD4+ T cells in the peritoneal cavity, but were rarely found in other compartments. Peritoneal CD49dhighCD4+ T cells were CD44highCD62Llow; expressed integrin α4β1 and CXCR3; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Access to the peritoneum from the circulation preferentially occurs through omental milk spots in an α4β7-dependent fashion, whereas entry to the peritoneal cavity is mediated by α4β1 as shown for B cells [44] and T cells [45]. Of note, almost all PCderived Th2 memory cells do express CD49d (subunit α4), which was also shown for PC-derived Th1 memory phenotype of CD4 + T cells [46]. CD49d can pair with β1 (not investigated in this study) or β7 (almost 50% of GATA3 + T cells express the integrin β7), and could have enabled the access of these cells to the PC.…”
Section: Discussionmentioning
confidence: 70%
“…Access to the peritoneum from the circulation preferentially occurs through omental milk spots in an α4β7-dependent fashion, whereas entry to the peritoneal cavity is mediated by α4β1 as shown for B cells [44] and T cells [45]. Of note, almost all PCderived Th2 memory cells do express CD49d (subunit α4), which was also shown for PC-derived Th1 memory phenotype of CD4 + T cells [46]. CD49d can pair with β1 (not investigated in this study) or β7 (almost 50% of GATA3 + T cells express the integrin β7), and could have enabled the access of these cells to the PC.…”
Section: Discussionmentioning
confidence: 70%
“…For example, although Tfh cells develop during the initial response to antigen through the events described above, it has also been shown that additional effector T helper cell subsets are capable of up‐regulating a Tfh‐like gene expression profile, making alternative Tfh developmental pathways plausible as well (Fig. ) . Similarly, studies have provided compelling evidence to suggest that differentiated Tfh cells are capable of up‐regulating gene expression programmes associated with alternative T helper cell types .…”
Section: The Multistage Process Of Tfh Cell Differentiationmentioning
confidence: 99%
“…1). [24][25][26][27] Similarly, studies have provided compelling evidence to suggest that differentiated Tfh cells are capable of up-regulating gene expression programmes associated with alternative T helper cell types. [28][29][30] Furthermore, it has been demonstrated that these multidirectional plasticity events in T helper cell populations are due in large part to an 'accessible' chromatin structure present at gene loci encoding key lineage-defining transcription factors, including Bcl-6.…”
Section: The Multistage Process Of Tfh Cell Differentiationmentioning
confidence: 99%
“…Given the inherent complexity of this process, many questions remain regarding the genesis of T FH cell populations. For example, while T FH cells can and do develop during the initial response to antigen, it has also been demonstrated that other effector T-helper cell subsets are capable of adopting a T FH -like profile, making a ‘post-effector' developmental pathway plausible as well 8 9 10 11 12 13 . These previous studies are important as they support the possibility that, in addition to effector T FH cells, other T-helper populations may assist in long-term antibody-mediated immunity by co-opting certain aspects of the T FH -cell gene program.…”
mentioning
confidence: 99%